(untitled) (Journal of Industrial and Mechanical Engineering, 2019)
The 33 parties that make up Buenos Aires Metropolitan Region own 36% of the country’s population and represent more than 60% of the Argentine industrial GDP, in just fewer than 4% of the territory of the Province of Buenos Aires. In this context, the La Matanza County, the most populated in the country and with the largest contribution to the provincial industrial GDP (22%), has been characterized by a long process of industrialization, which originates in the dawn of the industrialization of Argentina and this has greatly accompanied the evolution of the sector at the national level. The present work intends to carry out an analysis of this, both from the local and national perspective for the period 1930-2005.